2020
DOI: 10.1002/jez.2349
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced locomotor performance on familiar surfaces is uncoupled from morphological plasticity in Anolis lizards

Abstract: The radiation of Anolis lizards in the Caribbean is associated with a diversification of the functional match between morphology, habitat use, and locomotor performance.It has been hypothesized that the microhabitat a lizard is reared in can achieve a similar fit of form and function within a species. This predicts that plasticity in the locomotor apparatus is accompanied by changes in perching behavior or improved locomotor performance. To test this, we raised juveniles of two species (Anolis sagrei and Anoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…To test this hypothesis, we raised 45 male lizards of a trunk-crown ( Anolis carolinensis , adapted to climbing) and 71 male lizards of a trunk-ground ( A. sagrei , adapted to running) species on broad versus narrow surfaces until they reached adulthood ( Figure 4—figure supplement 2 ). The differences in the structural habitats promoted different styles of locomotion and perching behaviour ( Feiner et al, 2020 ). Both species belong to the Cuban clade and, therefore, the appropriate evolutionary divergence to compare against is the contrast between the respective ecomorphs in this clade on Cuba (trunk-ground [N Individuals = 20, N Species = 9] versus trunk-crown [N Individuals = 20, N Species = 9]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To test this hypothesis, we raised 45 male lizards of a trunk-crown ( Anolis carolinensis , adapted to climbing) and 71 male lizards of a trunk-ground ( A. sagrei , adapted to running) species on broad versus narrow surfaces until they reached adulthood ( Figure 4—figure supplement 2 ). The differences in the structural habitats promoted different styles of locomotion and perching behaviour ( Feiner et al, 2020 ). Both species belong to the Cuban clade and, therefore, the appropriate evolutionary divergence to compare against is the contrast between the respective ecomorphs in this clade on Cuba (trunk-ground [N Individuals = 20, N Species = 9] versus trunk-crown [N Individuals = 20, N Species = 9]).…”
Section: Resultsmentioning
confidence: 99%
“…To assess how well morphology predicts functional aspects related to fitness, we performed two trials that capture perching behaviour and locomotor performance in the lizards that were raised in the two microhabitats (see Material and methods). First, we assessed perching behaviour, and second, we scored running performance on broad and narrow surfaces (see Feiner et al, 2020 ) for more details). We have previously shown that locomotor performance was enhanced in the familiar microhabitat ( Feiner et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations